2019
DOI: 10.1039/c8nr10267h
|View full text |Cite
|
Sign up to set email alerts
|

Scalable fabrication of high-quality crystalline and stable FAPbI3thin films by combining doctor-blade coating and the cation exchange reaction

Abstract: This study highlights the importance of a scalable blade coating technique and the ion exchange reaction in fabricating high-quality perovskite thin films.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 62 publications
2
26
0
Order By: Relevance
“…Recently, we have demonstrated that high‐quality pinhole‐free films of the 2D perovskite 2‐phenylethylammonium lead iodide ((PEA) 2 PbI 4 ) can be fabricated using a scalable blade‐coating technique . Not only does this pave the way for the fabrication of large‐area devices based on 2D perovskites, but these films can also be used as excellent templates for the formation of high‐quality 3D perovskite films trough a cation exchange reaction . As such, blade‐coated films of 2D perovskite hold great potential for fabrication of large‐area perovskite layers for a wide variety of optoelectronic applications.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, we have demonstrated that high‐quality pinhole‐free films of the 2D perovskite 2‐phenylethylammonium lead iodide ((PEA) 2 PbI 4 ) can be fabricated using a scalable blade‐coating technique . Not only does this pave the way for the fabrication of large‐area devices based on 2D perovskites, but these films can also be used as excellent templates for the formation of high‐quality 3D perovskite films trough a cation exchange reaction . As such, blade‐coated films of 2D perovskite hold great potential for fabrication of large‐area perovskite layers for a wide variety of optoelectronic applications.…”
Section: Introductionmentioning
confidence: 99%
“…A previous research work has systematically demonstrated how the use of PEAI treatment enables the scalable fabrication of high‐quality perovskite film. [ 41 ] Similarly, we believe that the 3D/2D multi‐dimensional architecture of the perovskite film arising from the FPEAI treatment is highly beneficial for the scalable fabrication of PSCs. Large‐area PSCs of different A (0.2, 1.2, 2.0 cm 2 ) were prepared on 2.5 × 2.5 cm 2 ITO/glass substrate.…”
Section: Resultsmentioning
confidence: 99%
“…[47][48][49][50] As 2D perovskites are known to decompose under prolonged laser irradiation, [51] we first verified that no changes in the Raman spectrum are observed under the off-resonance excitation (785 nm) at a power and duration exceeding the typical acquisition time and excitation density used for Raman mapping ( Figure S3, Supporting Information). The average unpolarized Raman spectrum constructed from all (10.000) measured spectra were fitted by the sum of nine different Raman bands at frequencies of 20,28,35,40,44,56,73,83, and 98 cm À1 , as shown in Figure 2b. A complete list of all fitting parameters can be found in Table S1, Supporting Information.…”
Section: Resultsmentioning
confidence: 99%
“…Thin films of (PEA)2PbI4 were deposited on glass substrates through a one‐step blade‐coating process, according to a previously established recipe. [ 40 ] In the current work we focus our attention on the characterization of films that were cast from a stoichiometric precursor solution, as these were previously shown to exhibit excellent crystal quality and photoluminescence quantum yield superior to that of films cast from nonstoichiometric solutions. [ 41 ] The quality of the thus cast films was confirmed by the observation of very narrow (resolution‐limited) diffraction peaks in the X‐ray diffraction (XRD) pattern ( Figure a).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation